STRATEGI DAN MODE PEMERINTAH KOTA PALEMBANG DALAM MENERAPKAN KEBIJAKAN PEMBANGUNAN RUMAH MURAH BAGI MASYARAKAT BERPENGHASILAN RENDAH - Hamdi Darmawan; Ermaya Suradinata; Rossy Lambelanova; Sampara Lukman (GoAcademica Research dan Publishing, 2021)
According to our Constitution, every person has the right to physical and moral prosperity, to a home, and to a safe and stable living atmosphere. Residence plays a critical role in defining the nation's character and identity as part of the initiative to create a whole human being. However, not all Indonesian people can get a decent place to live as mandated by our constitution. Their small income causes them to be unable to buy a house which is getting more expensive. The city government of Palembang has launched a policy of low-cost housing for low-income communities (MBR). However, this policy has not been maximally successful. This study intends to find the right strategy and model in implementing the policy. This research uses a qualitative approach by making in-depth observations and a literature approach.